Surgical resection of a rapidly growing pulmonary spindle cell carcinoma by robot-assisted thoracoscopic surgery: a case report - Akihiro Koen; Hideyuki Maeda; Yoji Nagashima; Masato Kanzaki (Surgical Case Reports)
Abstract Background Pulmonary spindle cell carcinoma (PSCC) is an extremely rare tumor that is highly malignant and fast-growing. As chemotherapy and radiation therapy are ineffective, early surgical resection is effective for PSCC. Case presentation A 70-year-old woman with rheumatoid arthritis was referred to our hospital with an abnormal shadow. Chest computed tomography revealed a 33-mm-wide lobular mass in the right upper lobe. She was diagnosed with non-small cell lung cancer by bronchoscopic smear cytology. Although staging evaluation indicated stage IIIB (T3N2M0) disease, she required continued administration of immunosuppressants and prednisolone for rheumatoid arthritis. Therefore, robot-assisted thoracoscopic surgery (RATS) right upper lobectomy followed by lymph node dissection was performed without preoperative chemotherapy and radiotherapy. Pathological findings revealed PSCC. Conclusions We report a very rare case of pulmonary spindle cell carcinoma, successfully resected with RATS.